Implementing proposed reforms of the Mental Health Act for people with intellectual disability and autism: the perspective of multidisciplinary professionals in intellectual disability teams - Bharat Velani; Indermeet Sawhney; Regi T. Alexander; Sophie Shardlow; Asif Zia (BJPsych Open, 2022)
Background A recent government white paper sets out proposals for reforms to the Mental Health Act 1983 (MHA). Some of these proposals affect people with intellectual disabilities and/or autism.